The nexus of bookkeeping and tax compliance: A knowledge and skills assessment of barangay micro-entrepreneurs - Diaz, Rowell Agliones; Natividad, Nestor; Pascua, Isagani (Asian Development Policy Review, 2025)
The link between bookkeeping knowledge and skills and tax compliance practices of barangay micro-entrepreneurs in the Province of Nueva Ecija, Philippines, was empirically examined in this study. Using a descriptive-correlational design, information was obtained through a structured questionnaire from a sample comprising 182 micro-entrepreneurs operating in different barangays. Descriptive statistics were computed for bookkeeping and tax knowledge and skills, and Spearman's rank correlation analysis was applied to investigate the association between bookkeeping and tax compliance. Findings revealed moderate to high levels of bookkeeping knowledge and skills and a moderate extent of tax compliance practices for the respondents. There were moderate, statistically significant positive associations between overall bookkeeping knowledge and tax compliance (ρ = 0.48, p = 0.001) and overall bookkeeping skills and tax compliance (ρ = 0.52, p < 0.001). The research also found that, of all factors, the ability to keep books of accounts is significantly related to compliance with tax regulations and laws. Still, other variables and constraints affect adherence to tax laws. Specific interventions promoting financial literacy, simplified tax-related information, and enhanced support mechanisms are recommended to improve these small-scale businesses' bookkeeping activities and tax compliance.